2019
DOI: 10.1186/s12199-019-0763-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fatty pancreas and lifestyle on the development of subclinical chronic pancreatitis in healthy people undergoing a medical checkup

Abstract: BackgroundAlthough fat accumulation in human organs is associated with a variety of diseases, there is little evidence about the effect of a fatty pancreas on the development of subclinical chronic pancreatitis over the clinical course.MethodsWe conducted a prospective cohort study from 2008 to 2014 of patients who underwent a medical checkup consultation for fat accumulated in the pancreas. Patients included in the analysis were divided into a non-fatty pancreas group (n = 9710) and fatty pancreas group (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 48 publications
(48 reference statements)
1
23
0
2
Order By: Relevance
“…An earlier study from the United States found that individuals with chronic pancreatitis alone ( n = 35) had a significantly greater IPFD in comparison with controls ( n = 50) in a post-hoc analysis constrained to non-obese people only (body mass index < 30 kg/m 2 )[ 33 ]. A longitudinal study from Japan sought to investigate the temporal relationship between IPFD and chronic pancreatitis[ 34 ]. A total of 9933 individuals without pancreatitis were examined in 2008 and followed up for 4 years as part of their medical check-up.…”
Section: Excess Body Fatmentioning
confidence: 99%
See 1 more Smart Citation
“…An earlier study from the United States found that individuals with chronic pancreatitis alone ( n = 35) had a significantly greater IPFD in comparison with controls ( n = 50) in a post-hoc analysis constrained to non-obese people only (body mass index < 30 kg/m 2 )[ 33 ]. A longitudinal study from Japan sought to investigate the temporal relationship between IPFD and chronic pancreatitis[ 34 ]. A total of 9933 individuals without pancreatitis were examined in 2008 and followed up for 4 years as part of their medical check-up.…”
Section: Excess Body Fatmentioning
confidence: 99%
“…A total of 9933 individuals without pancreatitis were examined in 2008 and followed up for 4 years as part of their medical check-up. The presence of fatty pancreas disease at baseline was associated with a 3.9-times higher risk of incident pancreatitis during follow-up (odds ratio 3.9; 95% confidence interval 2.0 to 7.7), after adjustment for age, sex, body mass index, glycated hemoglobin, systolic blood pressure, alcohol abuse, tobacco smoking, and other covariates[ 34 ]. However, it is worth noting that transabdominal ultrasound was used in this study, which is suboptimal for diagnosing of both chronic pancreatitis and fatty pancreas disease.…”
Section: Excess Body Fatmentioning
confidence: 99%
“…18,19 The role of NAPS is still debatable in acute and chronic pancreatitis, pancreatic cancer, and pancreatic exocrine insufficiency. 20 Older age, high BMI, and insulin resistance are reportedly associated with NAPS, 9,12,21,22 although some studies have found no relation between NAPS and beta-cell function. 23 Fat infiltration of the pancreas may lead to more bleeding and post-operative fistula formation in pancreatic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, this is also a challenge in obese patients to exhibit an apparent pancreas[ 44 ]. Pancreatic fat accumulation appears hyperechoic as compared with liver or kidney accumulation, a reference point for diagnosis[ 45 , 46 ]. Some studies have established that echogenicity of retroperitoneal fat suggests a higher amount of pancreatic fat deposition, using a grading system[ 22 , 25 , 7 ].…”
Section: Diagnosis Of Nafpdmentioning
confidence: 99%